2020
DOI: 10.1073/pnas.1909814117
|View full text |Cite
|
Sign up to set email alerts
|

Decision between mitophagy and apoptosis by Parkin via VDAC1 ubiquitination

Abstract: VDAC1 is a critical substrate of Parkin responsible for the regulation of mitophagy and apoptosis. Here, we demonstrate that VDAC1 can be either mono- or polyubiquitinated by Parkin in a PINK1-dependent manner. VDAC1 deficient with polyubiquitination (VDAC1 Poly-KR) hampers mitophagy, but VDAC1 deficient with monoubiquitination (VDAC1 K274R) promotes apoptosis by augmenting the mitochondrial calcium uptake through the mitochondrial calcium uniporter (MCU) channel. The transgenic flies expressing Drosophila Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 63 publications
(62 reference statements)
2
102
0
Order By: Relevance
“…Alterations in mitochondrial calcium uptake can lead to oxidative stress or calcium overload triggering cell death (72)(73)(74). Interestingly, several recent studies have revealed a role of increased mitochondrial calcium levels in promoting neurodegenerative phenotypes (75)(76)(77)(78)(79). For example, in Drosophila and zebra sh, it was found that mutations in the genes encoding the PINK1 ortholog results in elevated mitochondrial calcium, and when mitochondrial calcium was reduced in these mutants neurodegeneration was prevented (80,81).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in mitochondrial calcium uptake can lead to oxidative stress or calcium overload triggering cell death (72)(73)(74). Interestingly, several recent studies have revealed a role of increased mitochondrial calcium levels in promoting neurodegenerative phenotypes (75)(76)(77)(78)(79). For example, in Drosophila and zebra sh, it was found that mutations in the genes encoding the PINK1 ortholog results in elevated mitochondrial calcium, and when mitochondrial calcium was reduced in these mutants neurodegeneration was prevented (80,81).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, beyond compensatory or synergistic effects, the ubiquitylation state of VDAC was shown to differentially affect either mitophagy or apoptosis. While polyubiquitylated VDAC1 is able to induce mitophagy, monoubiquitylated VDAC1 seems to exert a protective effect over apoptosis (Ham et al, 2020). However, the conditions by which VDAC gets mono or polyubiquitylated and the respective E3 ligases involved are still to be identified.…”
Section: Pro-apoptotic Effects Of Mitophagymentioning
confidence: 99%
“…Parkin has been reported to specifically target the pro-survival BCL-2 protein MCL-1 for proteosomal degradation (Figure 4; Carroll et al 2014;Zhang et al 2014). In a recent study, Ham et al (2020) propose that the decision between mitophagy or apoptosis induction by Parkin depends on the ubiquitination of VDAC (Figure 4; Ham et al 2020). It has been proposed that Parkin either mono-or polyubiquitinates VDAC1.…”
Section: Parkin Activation Can Both Prevent and Promote Cell Deathmentioning
confidence: 99%